Towards African humanicity: Re-mythogolising Ubuntu through reflections on the ethnomathematics of African cultures - Chahine, Iman C (Critical Studies in Teaching and Learning, 2023)
Throughout the history of mathematics, Eurocentric approaches in developing and disseminating mathematical knowledge have been largely dominant. Building on the riches of African cultures, this paper introduces ethnomathematics as a discipline bridging mathematical ideas with cultural contexts thereby honoring diversity and fostering respect for cultural heritages. Ethnomathematics promotes a conceptualisation of culture to include the authentic humanity of the people sharing collective beliefs, traditions, and practices. I propose the term African humanicity to refer to the authentic African experience that reflects genuine African cultural identity. I further argue that immersion in the ethnomathematical practices of African cultures provides insight into critical factors shaping African students’ success in mathematics. Drawing upon the vast literature on the ingenuity of African cultures, I present ethnomathematical ideas that permeate numerous African indigenous knowledge systems that could be introduced in the mathematics curriculum. These systems include folk games and puzzles, kinship relations, and divination systems.